The enhancement of astaxanthin production in Phaffia rhodozyma through a synergistic melatonin treatment and zinc finger transcription factor gene overexpression - Jia, Jianping; Chen, Zhitao; Li, Qingqing; Li, Feifei; Liu, Siru; Bao, Guoliang (Frontiers in Microbiology, 2024)
Astaxanthin has multiple physiological functions and is applied widely. The yeast Phaffia rhodozyma is an ideal microbial astaxanthin resource. However, the stress conditions beneficial for astaxanthin synthesis often inhibit cell growth, leading to a low productivity of astaxanthin in this yeast. In this study, 1 mg/L melatonin (MT) could increase the biomass, astaxanthin content and yield in P. rhodozyma by 21.9%, 93.9% and 139.1%, reaching 6.9 g/L, 0.3 mg/g DCW and 2.2 mg/L, respectively. An RNA-seq-based transcriptomic analysis showed that MT could disturb the transcriptomic profile of P. rhodozyma cell. Further differentially expressed genes (DEGs) analysis show that the genes induced or inhibited significantly by MT were mainly involved in astaxanthin synthesis, metabolite metabolism, substrate transportation, anti-stress, signal transduction and transcription factor. A mechanism of MT regulating astaxanthin synthesis was proposed in this study. The mechanism is that MT entering the cell interacts with components of various signaling pathways or directly regulates their transcription levels. The altered signals are then transmitted to the transcription factors, which can regulate the expressions of a series of downstream genes as the DEGs. A zinc finger transcription factor gene (ZFTF) as one of the most upregulated DEGs induced by MT was selected to be overexpressed in P. rhodozyma.It was found that the biomass and astaxanthin synthesis of the transformant were further increased compared to those in MT-treatment condition. Combining MT-treatment and ZFTF overexpression in P. rhodozyma, the biomass, astaxanthin content and yield were 8.6 g/L, 0.6 mg/g DCW and 4.8 mg/L, and increased by 52.1%, 233.3% and 399.7% than those in the WT strain under MT-free condition. In this study, the synthesis and regulation theory of astaxanthin is deepened, and an efficient dual strategy for industrial production of microbial astaxanthin is proposed.